2022
DOI: 10.3390/en15051815
|View full text |Cite
|
Sign up to set email alerts
|

Delightful Daylighting: A Framework for Describing the Experience of Daylighting in Nordic Homes and Coupling It with Quantitative Assessments

Abstract: In this conceptual article we propose a framework for describing the experience of delightful daylighting in Nordic homes and a method to correlate it with an existing quantitative daylighting assessment. In contrast to earlier research on daylighting, the present work gives priority to developing the methodology for researching the experience of the inhabitant in a real situation and relying the quantitative assessment on an existing method. In this way, we shift the focus of daylight studies from quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A recent study concerning the perception of daylight from a qualitative perspective highlighted the importance of such assessment since most studies focus on the light's functionality, performance, and efficiency and neglect the human experience. Also, it demonstrated that only 7% of the studies were conducted on residential spaces, and another 2% were in higher latitudes than 60°N (Vikberg et al, 2022). As a result, it excludes the Nordic population that could potentially benefit from technologies such as sunlight simulators.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study concerning the perception of daylight from a qualitative perspective highlighted the importance of such assessment since most studies focus on the light's functionality, performance, and efficiency and neglect the human experience. Also, it demonstrated that only 7% of the studies were conducted on residential spaces, and another 2% were in higher latitudes than 60°N (Vikberg et al, 2022). As a result, it excludes the Nordic population that could potentially benefit from technologies such as sunlight simulators.…”
Section: Introductionmentioning
confidence: 99%